The limbs factory: Circuits of fear and hope and the political imagination on the Western Sahara - Yousfi, Kenza (AUC Knowledge Fountain, 2015)
The wall, as a practice and an imagination, involves an engagement with modes of producing fear in the contemporary moment. This research explores the relationships between the walling imagination in the weaponized field of the Moroccan-built wall in the Western Sahara and the political in its making of the present. The question I explore ethnographically is: What are the ways in which the political is perpetually enacted vis-à-vis the walling imagination? From my ethnographic site—the Saharawi refugee camps—I engage with Saharawi everydayness in navigating violent structural confinements: the wall, the camp, the national liberation master plan, and the performances of refugeeness. My argument goes beyond the historical formation of the Saharawi national liberation movement to look at the constituents of the political laboratory concerned with experimenting with the permanent present. In this formulation, the aesthetics of violence in the Western Sahara are of a global logic whereby violence in its walling modality doesn’t exist outside of capital. The making of the present does not become about the past or the future, but rather about experimenting with the different existing structures Saharawis navigate